Rumbo al Gran Banco: una etnohistoria de la pesca industrial del bacalao en los Bancos de Terranova - García Orellán, Rosa (Eusko Ikaskuntza-Sociedad de Estudios Vascos, 2006)
[ES]Rumbo al Gran Banco parte de los comienzos de la pesca industrial del bacalao española en el primer tercio del siglo XX, la situación que allí encontraron, los avatares humanos y los avances tecnológicos que se van incorporando, la Guerra Civil y la guerra mundial, la bonanza pesquera, la incorporación de las parejas, la concurrencia, así como la exploración de todo el Gran Banco. La gestión por parte de Canadá de las doscientas millas marinas y la moratoria del bacalao. También se presenta la historia de la pesca en Galicia y Terranova a lo largo de todo el siglo XX, dos territorios que comparten el mismo océano y una mirada puesta en la mar. [EN]Rumbo al Gran Banco traces the history of the Spanish Grand Banks cod fishery from its origins in the first third of the twentieth century. It begins by t reating the general socio-economic background; the people involved; the evolving technology they used; and the effects of the Civil War and World War II. The article then considers the effects of the fishing bonanza, the introduction pair-trawlers and the competition that came to characterize this fishery, including the exploration of the entire extent of the Banks in the search for cod. The historic survey concludes with an examination of the effects of, first, Canada;s 200-mile EEZ and, later, the moratorium imposed on the cod fishery on Canada’s Grand Banks. As well, the article looks specifically at the history of the fishery in general in Newfoundland and Galicia, which share both an ocean and a seaward vision.